Mobile Banking Service Strategy of Indonesian Syariah Bank (SOAR Analysis Study by Stavros, Cooperrider and Kelly) - Eva Walanda Setyoningrum; Sundari; Rahma Sandhi Prahara (Create: Journal of Islamic Management and Business, 2025)
Digital banking services through mobile banking platforms provide convenience, effectiveness, and efficiency for customers in conducting digital transactions via mobile phones and the internet. The method used to analyze data in the field is SOAR analysis, which aims to determine the company's strategy based on internal and external factors in order to achieve the goals of mobile banking services. SOAR analysis includes four main elements: strengths, opportunities, aspirations, and results. Based on this background, the formulation of the problem proposed is how is the strategy of PT. Bank Syariah Indonesia (BSI) based on SOAR analysis, with the aim of analyzing PT. Bank Syariah Indonesia's mobile banking services using SOAR analysis. This study uses a qualitative research method, with primary and secondary data. Data collection techniques are carried out through interviews, observations, and documentation. The data analysis technique used is SOAR analysis. The results of research in the field show that BSI's mobile banking services can help and facilitate customer banking activities only through mobile phones that can be done anytime and anywhere. The results of the SOAR analysis show that the strengths of BSI's mobile banking services include transactions that can be done anywhere, time efficiency, ease of transactions, card management features, fast information services, and easy mobile banking activation via mobile phones. The opportunities include the implementation of new technologies through IT development, expansion of BSI services to the international market, and aspirations to be able to check monthly accounts and activate services independently. The result of this analysis is an increase in services on the BSI mobile application, which makes it easier for customers to use the BSI mobile application and increase the number of BSI mobile users.